Understanding Rural Perspectives and Practices of Health in Banggai Laut, Indonesia - Ary Anggara; Ressy Dwiyanti; Rosa Dwi Wahyuni; Rahma; Vera Diana Towidjojo; Sarifuddin; Aristo; Mochammad Hatta; M. Sabir; Muh. Ardi Munir; Tri Setyawati; Muhammad Nasir (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
Health is always an important value for human beings and the most fundamental condition of life. Health is perceived differently influenced by many factors including education, experience, knowledge, culture, and environment. The study aimed to explore community perception of health, including causes of diseases, and choices of help for health problems in rural setting in Central Sulawesi, Indonesia. The study is a qualitative ethnography with several data collection methods including semi structured in-depth interviews, small group discussion, informal conversations, photography, and direct observation. Study location was in Bangkurung sub-district. The study found that health is perceived as a power, energy, normal physiology of human body, and ability to work normally. Participants understood and believed that health is influenced by many factors including environment, food, lifestyle, social interaction and the rise of megycism, traditionally prohibited behaviors, religious belief, mind, and workload. Community members commonly used both medical treatment and traditional healing methods.